Caracterização funcional de um composto capaz de regular o desenvolvimento celular de Trypanosoma cruzi - Araujo Junior, Adalberto Miguel De [UNIFESP] (2019)
Chagas disease, caused by the kinetoplastid parasite Trypanosoma cruzi, remains one of the most neglected tropical illnesses in the world. Approximately 6 to 7 million people worldwide are estimated to be infected with T. cruzi. Benznidazole (BNZ) and nifurtimox (NFX), the only drugs available to treat the disease, are associated with severe side effects and unclear efficacy on the chronic phase of infection. The pathogenesis related to such disease is still poorly understood, which reinforces the importance of researching more about the basic biology of T. cruzi infection, replication and differentiation, once only this way new strategies of chemotherapies will be discovered. In the absence of clinically validated molecular drug targets, development of novel phenotypic screening assays may result in the discovery of compounds that can inducephenotypes related to distinct mechanisms of action not investigated so far. In this report, we attempted to discuss how relevant the phenotypic screening approach can be for the understanding of T. cruzi cell biology. From the high content screening of a library of 4,000 putative kinase inhibitors, we selected some compounds of interest, which showed low cytotoxicity and capacity to induce specific phenotypes of interference in the normal intracellular development of the parasite. One of such compounds (named HF) inhibited the parasite replication without causing loss of cell viability. The functional characterization of the HF activity showed that: (i) the phenotype of intracellular development arrest was not restricted to a host cell type; (ii) the compound was able to inhibit the replication of different T. cruzi strains (Y, Sylvio X10/1 e CL Brener strain); (iii) the phenotype of arrest was reversible upon compound removal, once the parasite from that point grows normally concluding its intracellular cycle by differentiation to trypomastigotes; (iv) the compound did not show cytotoxicity for distinct host cells (U2OS, LLC-MK2, NRK-52E and BHK-51) for up to the maximum concentration of 100 µM for 48 h, being highly selective for the parasite; (v) the molecule also was able to induce arrest in the epimastigote form of T. cruzi without causing loss of viability up to 96 h, but displayed a dose-dependent cidal activity against bloodstream forms of Trypanosoma brucei and promastigote forms of Leishmania donovani; and (vi) the compound caused T. cruzi cell cycle arrest, being the most of the cell population at G1, unlike what was observed in cells treated with benznidazole. Altogether, these results suggest that this compound acts via a regulator of cell cycle that can specifically cause arrest in T. cruzi and not in mammalian cells. Regarding the other trypanosomatids, there may be a regulation of the cell cycle by the compound, however we did not observe the same phenotypic action as seen in T. cruzi. Moreover, this work has shown us the potential of HF to be applied as a chemical probe in investigations regarding T. cruzi replication and development.